Sketsa Normatif dan Empirik Persoalan Negara dan Pemerintahan di Kalangan Umat Islam - Ridwan HR (Fakultas Hukum Universitas Islam Indonesia, 2003)
The state institution and the government in Islam is the instrument of application of the part in Islamic tenet. Because the part of Islamic tenet have to be applied in human life, whilefor the application of Islamic tenet need the state instrument and government, so the existence of this instrument is unavoidable. The Moslem must create the model, form, state system and government according with the situation and condition faced by theMoslem. The Islamic tenet teach only the general principles on state establishment and running the government. Now, the form, model and system of state and government is applicable, as long as it relevant with the principles of Islamic tenet